- TINDAK PIDANA PENGGELAPAN TERKAIT DALAM HUBUNGAN PEKERJAAN (PUTUSAN NOMOR:46/PID.B/2021/PN.WGP) : - - Jhansen Valix Hutapea; Maria Silvya E. Wangga (Faculty of Law, Universitas Trisakti, 2024)
Embezzlement committed by adults is a crime that is very troubling to society because it results in significant losses. The formulation of the problem of this article is whether the act of embezzlement committed by a person due to his employment relationship meets the formulation in Article 372 of the Criminal Code? and how is the determination of the conviction of the perpetrator who committed embezzlement in the employment relationship in the court decision Number:46/Pid.B/Pn.Wgp. The research method is normative with the nature of descriptive analytical research, the type of data used is secondary data, quantitative data analysis, and conclusions based on the deductive method. The results showed that the acts of perpetrators of embezzlement of cattle by Augustine Taka Njanji against Melkianus Damu Patimara do not meet the elements of Article 372 of the Criminal Code because the core offense of Article 372 of the criminal code is only ordinary embezzlement and its general nature, the appropriate article should be Article 374 of the Criminal Code because the perpetrator and victim are bound by an employment relationship. The conclusion is the Afghan government's responsibility for the conflict is to protect civil society and provide compensation to the victims